THE ANALYSIS OF DYNAMIC RESPONSE AND VOLTAGE FLICKER WITH STATCOM ON DISTRIBUTION NETWORK - Brahmaiah, V.Siva; Adhikari, Manav (International Journal of Engineering Technologies and Management Research, 2017)
The Flexible Alternating Current Transmission Systems (FACTS) device deals with the control of power flow, alternating current of transmission line and immediately respond towards the stability problems of the system. The present paper show that how the FACTS device STATCOM enhance the dynamic response and voltage flicker in distribution network of the power systems. In MATLAB a simplified distribution system is modeled and the find out the desired objectives. D-STATCOM changes from inductive to capacitive operation, the modulation index of the PWM inverter is increased from 0.56 to 0.9 which corresponds to a proportional increase in inverter voltage. Reversing of reactive power is very fast, about one cycle, as observed on D-STATCOM current. Observed on Scope that voltage fluctuation at bus B3 is now reduced to +/- 0.7 %. The D-STATCOM compensates voltage by injecting a reactive current modulated and varying between 0.6 pu capacitive when voltage is low and 0.6 pu inductive when voltage is high.